Migration Mapper: Identifying movement corridors and seasonal ranges for large mammal conservation - Jerod A. Merkle; Josh Gage; Hall Sawyer; Blake Lowrey; Matthew J. Kauffman (Methods in Ecology and Evolution)
Abstract Modern tracking technology has facilitated a novel understanding of terrestrial mammal movement while revealing that movements are being truncated and lost. The first step towards conserving mobile animals is identifying movement corridors and key seasonal ranges. Yet, the identification and subsequent mapping of these important areas has remained a challenge due to the analytical skills necessary to conduct such analyses. Migration Mapper (MM) is a user‐friendly software that provides tools to analyse global positioning system (GPS) collar data to create season‐specific, population‐level polygons representing areas where most of a population moves (i.e. movement corridors) and areas where most of a population spends time (e.g. high‐use areas, seasonal ranges). MM consists of six standalone modules including data cleaning and review, seasonal movement delineation, movement model application, calculation of population‐level outputs and visualization of results. Analysis of GPS data using MM can provide the spatial polygons necessary to facilitate conservation and policy planning. New initiatives at the local and global levels are already beginning to use MM to facilitate conservation of large, terrestrial mammals.